PENGUKURAN KINERJA KARYAWAN DENGAN MENGGUNAKAN METODE HUMAN RESOURCE SCORECARD DI PT GANDA NUSANTARA PERSADA - Nurmansyah, Nurmansyah; Asmarawati, Citra Indah (LPPM Universitas Putera Batam, 2021)
The condition of a company is very dependent on the quality of its human resources. Increasing the company's competitiveness must begin with improviment the quality of existing human resources first. To improve the quality of human resources can be done by increasing work motivation, work discipline and skills training. Before improving the quality of the people, there must first be a performance measurement system to be able to see the existing performance conditions. Performance measurement research conducted at PT. Ganda Nusantara Persada was conducted by applying the Human Resource Scorecard research method. In the Human Resource Scorecard method, research is carried out by processing data that considers the financial perspectif, customer perspectif, internal business process perspectif and growth and learning perspectif. From the output from this research conducted at PT. Ganda Nusantara Persada shows that from the four perspectives, the company's condition is good. However, when viewed from the comparison of the Idel value and the Belief value, there are still significant differences in several indicators, it is necessary to evaluate the existing performance quality.